Videogame Production: How the Capitalist Socius and Platformization Subjectivate - Jackson, Joshua (Loading)

(untitled) (Canadian Game Studies Association, 2019)
Diverse representations of bodies in videogames has become a point of contention among developers and consumers alike, which has lead scholars to question why videogame production is breaking with trends of recognizable, anthropocentric characters in favor of “diverse” bodies. This paper contends that the overarching reason for this is that the capitalist socius (Deluze and Guattari, 1986) has become more readily equipped to be able to monetize and streamline diversity away from being an act of subversion and into an easily manipulatable source of revenue. In examining how the capitalist socius overlays onto the videogame production process, a few things become apparent. Because videogame production operates within the capitalist socius, their goals are the similar: to become autopoietic (able to reach a point of homeostasis in which the entity is able to reproduce and maintain its structural integrity) and to turn any and all resources into sources of capital generation. The expectation of bodies working in these regimes is to be as non-threatening and as pliable to new modes of subjectivation and capital generation as possible, but that means that bodies must undergo certain political transformations to adhere to these needs of the capitalist socius and videogame production process. As with any hegemonic structure, there are pockets of resistance that look to buck the current trends of subjectivation and capital generation. The form of resistance this paper examines is personal-games and affective experiences, but as with most things pertaining to the capitalist socius, personal-games are dangerously close to being swept up, monetized, and crunched down.